The Integration of Problematic Teaching Method and Innovation in Education - Fayzullaev Sh. N; Eshnazarova G (Universitas Muhammadiyah Sidoarjo, 2018)
This article analyzes the content of the educational content linking the problematic teaching methodology with information and pedagogical technologies, interactive teaching methods in the teaching of future teachers and coaches in order to implement the pre-school education reform and the requirements of this sector. It also focuses on creating a psychological environment that is related to achieve designing the learning processes.